Development of an Algorithm to Determine the Most Efficient Trajectories in Directional Wells - R.R. Francisco; M. Bertuzzi; G.V.V. Ramlov; L.A. Alves; C.E. Metzler (Revista Brasileira de Ensino de Física, 2025)
We present the development of an algorithm designed to determine the most efficient trajectories for directional wells, a key method used in oil and gas extraction. The primary goal is to optimize the trajectory by minimizing the tension and torques applied to the drill column during drilling operations while ensuring the well stability and operational efficiency. The algorithm analyzes Type I well trajectories, focusing on identifying the best combination of trajectory radius, section length, and inclination angles. To achieve this, the model is based on fundamental principles of mechanics and takes into account factors such as well geometry and the neutral buckling point to define the drill collar length required to avoid structural failures. This algorithm has potential applications in academic research and industry to improve directional drilling strategies, as it can also be used as an educational tool in engineering and applied physics courses.